Optimization of Artificial Intelligence in Islamic Religious Education: Opportunities and Challenges in Learning Evaluation - Awalia Rina Rahmawati; Risfita Wulandari; Sadaruddin, Maulida Ade Suryani; Mustofa, Triono Ali; Chedimae, Hamdan (Universitas Muhammadiyah Surakarta, 2025)
In the era of digital transformation, artificial intelligence (AI) has become important innovation in the world of education, including in the evaluation of learning Islamic Religious Education. This research aims to examine the optimization the application of AI in Islamic Religious Education evaluation, the challenges faced, and the future potential the future. With a qualitative approach based on literature review, this research analyzing literature related to the application of AI in the context of Islamic education. Results The study shows that AI is capable of enhancing the effectiveness of evaluating cognitive aspects. Cognitive through digital quizzes and real-time data analysis systems, as well as starting reaching affective and psychomotor aspects with technology such as chatbots, facial recognition, and virtual reality. However, a number of challenges also arise, among others, the limitations of AI in capturing the spiritual dimension, the potential for algorithmic bias algorithmic, ethical and data privacy issues, as well as teacher readiness and infrastructure. In the future, AI has great potential to become a comprehensive and personal, if the application of AI in learning and evaluation can be supervised in an ethical and still making teachers the central figure in the formation of values and character. This research recommends a synergy between technology developers, educators, and Sharia experts in developing a human-centered AI-based evaluation system and in accordance with Islamic values.